Analisis Peraturan Bupati No 27 Tahun 2018 tentang Penanggulangan HIV/AIDS di Kecamatan Krian, Kabupaten Sidoarjo - Vanni Alivyah Krisnandela; Lukman Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation of HIV/AIDS response policies in Krian District, Sidoarjo Regency, based on Sidoarjo Regent Regulation No. 27 of 2018. The method used is qualitative descriptive with data collection techniques through interviews, observation, and documentation. The results of the study show that the implementation of HIV/AIDS response policies in Krian Subdistrict has been carried out through six main aspects, namely health promotion, HIV prevention, HIV diagnosis testing, treatment, care and support for people living with HIV/AIDS, HIV surveillance, and rehabilitation. The program implementation has generally been running well and has involved various parties such as the Krian Community Health Center, the Health Office, and the Delta Crisis Center NGO. However, the effectiveness of policy implementation still needs to be improved, especially in terms of human resource availability, funding allocation, and cross-sector coordination. The study results show that social environmental factors and the existence of localized areas also influence the increase in the number of HIV/AIDS cases in Krian District, so efforts to strengthen cross-institutional collaboration and optimize resources are needed so that HIV/AIDS prevention in the area can be more effective and sustainable.